2021
DOI: 10.3389/fmed.2021.651938
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Flora Changes in Cesarean Section Uterus and Its Possible Correlation With Inflammation

Abstract: Background: It has not been fully elucidated whether the change of the uterus flora is correlated to impaired fecundity. This case-control study aimed to analyze the differences in uterus microbial flora between women with post-cesarean section (CS) scar diverticulum (PCSD) (CS group) and women after vaginal delivery (control group), exploring the correlation between differentially expressed microbial flora and inflammation.Methods: Infertile women who underwent hysteroscopy were enrolled in this case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The fluid which may be caused by the history of caesarean section and further influence of microbial flora changes could be of major importance. Additionally, we have conducted another prospective study which analysed the differences in uterus microbial flora between women with post-caesarean section (CS) scar diverticulum and women after vaginal delivery, exploring the correlation between differentially expressed microbial flora and inflammation and found that the disrupted uterus microbiota composition in women with CS may be closely associated with local inflammation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fluid which may be caused by the history of caesarean section and further influence of microbial flora changes could be of major importance. Additionally, we have conducted another prospective study which analysed the differences in uterus microbial flora between women with post-caesarean section (CS) scar diverticulum and women after vaginal delivery, exploring the correlation between differentially expressed microbial flora and inflammation and found that the disrupted uterus microbiota composition in women with CS may be closely associated with local inflammation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with the controls, there was a lower lactobacillus-dominating percentage in the CS group. This change could be a sign of chronic endometritis [ 11 ]. Our findings further confirmed this suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the persistent uterine effusion may further cause localized inflammation of the endometrial tissue [ 9 ]. Chronic endometritis (CE) is described as a localized edematous inflammation of the uterine mucosa [ 10 ], which can affect endometrial receptivity, implantation, and pregnancy outcomes [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unique microbial community composition in the female reproductive tract is essential in maintaining female reproductive health [8][9][10]. Our previous studies have demonstrated that the abnormal alterations in the local microbiota of Cesarean scar defects (CSD) cause continuous leakage through local inflammation and immune imbalance [11]. Further investigations of ours revealed the underlying mechanism demonstrating that abnormal bacteria in CSD deplete protective fatty acids and generate N-(3-hydroxy-eicosanoyl)-homoserine lactone, thus leading to promoting apoptosis of vascular endothelial cells and endometrial epithelial cells, ultimately impairing women's reproductive capacity [12].…”
Section: Introductionmentioning
confidence: 99%